The Effect of Quality of Work Life and Human Resource Development on the Performance of Employees in the Bandung City Health Department - Asep Wahyu; Rima Rahmayanti (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2025)
The study aims to analyze Quality of work life, human resource development and employee performance at the Bandung City Health Office, as well as the influence of Quality of work life and human resource development on employee performance at the Bandung City Health Office. This study is a quantitative study with a causal approach that explains the causal relationship between research variables using hypothesis testing. Respondents in this study were 303 employees of the Bandung City Health Office and UPT within the Bandung City Health Office. Data collection used a questionnaire measured using a Likert scale. Instrument testing used validity and reliability tests. Data analysis used multiple linear regression analysis, classical assumption tests and hypothesis tests. The results of the study showed that (1) human resource development had a significant effect on employee performance, (2) quality of work life had a significant effect on employee performance. (3) human resource development and quality of work life had a significant effect on employee performance.